Cardiac arrhythmogenesis: roles of ion channels and their functional modification - Lei, Ming; Salvage, Samantha C.; Jackson, Antony P.; Huang, Christopher L.-H. (Frontiers in Physiology, 2024)
Cardiac arrhythmias cause significant morbidity and mortality and pose a major clinical health problem. They arise from disruptions in the normally orderly propagation of cardiac electrophysiological activation and recovery through successive cardiomyocytes in the heart. They reflect abnormalities in automaticity, initiation, conduction or recovery in cardiomyocyte excitation. The latter properties are dependent on electrophysiological, surface membrane, mechanisms underlying the cardiac action potential. Their disruption results from spatial or temporal instabilities and heterogeneities in generation and propagation of cellular excitation. These arise from abnormal function in their underlying surface membrane, ion channels and transporters, and in the interactions between them. The latter in turn form common regulatory targets for the hierarchical network of diverse signalling mechanisms reviewed here. Additional to direct molecular level pharmacological or physiological actions on these surface membrane biomolecules, accessory, adhesion, signal transduction, and cytoskeletal anchoring proteins modify both their properties and localization. At the cellular level of excitation-contraction coupling processes, Ca2+ homeostatic and phosphorylation processes affect channel activity and membrane excitability directly or through intermediate signalling. Systems-level autonomic cellular signalling exerts both acute channel and longer term actions on channel expression. Further upstream intermediaries from metabolic changes modulate the channels both themselves and through modifying Ca2+ homeostasis. Finally, longer term organ-level inflammatory and structural, fibrotic and hypertrophic, remodelling similarly can influence all these physiological processes with potential pro-arrhythmic consequences. These normal physiological processes may target either individual or groups of ionic channel species, and alter with particular pathological conditions. They are also potentially alterable by direct pharmacological action, or effects on longer term targets modifying protein or cofactor structure, expression or localization. Their participating specific biomolecules, often clarified in experimental genetically modified models, thus constitute potential therapeutic targets. The insights clarified by the physiological and pharmacological framework outlined here provide a basis for a recent modernized drug classification. Together they offer a translational framework for current drug understanding. This would facilitate future mechanistically directed therapeutic advances, for which a number of examples are considered here. The latter are potentially useful for treating cardiac, in particular arrhythmic, disease.